Containing Ontario's hospital costs under universal insurance in the 1980s: what was the record? - Detsky, A S (1990)
In recent years the Ontario government has been concerned that the proportion of public expenditures devoted to health care is at an all-time high. In addition, the media have devoted considerable attention to specific incidents that may represent inadequate funding of hospital services. To shed light on the debate on health care expenditures we analysed the trend in expenditures of Ontario's hospital sector in the 1980s in terms of the amount of inputs (e.g., labour) used to produce hospital services (e.g., a patient-day or admission) and after adjustment for general inflation. As in the 1970s the number of inputs grew relatively slowly during the 1980s. Inputs per patient-day grew at an annual rate of 0.46% and inputs per admission at an annual rate of 2.4%. Cost increases were largely accounted for by hospital wage increases; this could have been due to Ontario's rapidly expanding economy. These findings indicate that Ontario has continued to be successful in containing the number of inputs used in the hospital sector. However, after two decades of substantial success with publicly acceptable cost control, the government faces increased scrutiny as the media and the public focus attention on several areas of perceived inadequate funding in health care services.